Occurrence of Albifimbria verrucaria in the Blood of a Female Child With Neuroblastoma - Masetti, Riccardo; Prodi, Antonio; Liberatore, Andrea; Carfagnini, Filomena; Cappelletti, Eleonora; Leardini, Davide; Pession, Andrea; De Carolis, Elena; Cricca, Monica (Frontiers in Medicine, 2020)
We report the first case of bloodstream infection (BSI) due to Albifimbria verrucaria in a pediatric patient affected by neuroblastoma (NBL). We collected two serial positive blood cultures from a central venous catheter and we isolated a slow growing filamentous fungus, named Albifimbria verrucaria. The identification was obtained by comparison of partial β-tubulin gene sequence. At CT scan, we observed few persistent lung small round lesions, with ground glass features, not responsive to chemotherapy. Antifungal susceptibility testing (AST) showed elevated MIC values for itraconazole (2 µg/ml), fluconazole (256 µg/ml) and echinocandins (>8 µg/ml). Itraconazole-tolerant strains were already been reported in agriculture. Albifimbria genus comprises common soil-inhabiting and saprophytic fungi, in particular A. verrucaria has been isolated as plant pathogen in Northern and Southern Italy. Recently, it has been recognized as causative agent of keratitis in humans. In conclusion, we describe an unprecedented fungemia by A. verrucaria and we show as an unexpected environmental pathogen may cause invasive fungal infection in an immunocompromised host.